Distinctive metabolomic fingerprint in scleroderma patients with pulmonary arterial hypertension. (15th August 2017) - Deidda, Martino; Piras, Cristina; Cadeddu Dessalvi, Christian; Locci, Emanuela; Barberini, Luigi; Orofino, Susanne; Musu, Mario; Mura, Mario Nicola; Manconi, Paolo Emilio; Finco, Gabriele; Atzori, Luigi; Mercuro, Giuseppe
Abstract: Background: Pulmonary arterial hypertension (PAH) in systemic sclerosis (SS) identifies a poor prognosis subset of patients. Recent studies suggested a "metabolic theory" on the development of pulmonary arterial hypertension. On this basis we performed a metabolomic study in order to evaluate whether differences in pulmonary arterial blood metabolites were identifiable in SS patients with increased pulmonary vascular resistance (PVR). Methods: We studied 18 SS patients (age 58.7 ± 15.6 years) free of pulmonary fibrosis who underwent a right heart catheterization (RHC). A blood sample was collected during the RHC in the distal peripheral circulation of the pulmonary arteries to perform the metabolomic analysis. Results: Based on PVR we divided the population into Group A ( n  = 8; PVR = 1.16 ± 0.23 WU) and Group B ( n  = 10; PVR = 2.67 ± 0.67 WU; p  < 0.001 vs Group A). No significant differences were identified in terms of anthropometric, clinical, echo and therapeutic characteristics. At RHC the 2 groups showed a difference in mean pulmonary pressure values (Group A: 20 ± 4 mm Hg; Group B: 27 ± 3.4 mm Hg; p  = 0.03), with mild PAH in Group B. We applied an OSC–PLS–DA with a clear clusterization; SSc patients with PAH showed an increase in acetate, alanine, lactate, and lipoprotein levels and a decrease in γ-aminobutyrate, arginine, betaine, choline, creatine, creatinine, glucose, glutamate, glutamine, glycine, histidine, phenylalanine, and tyrosine levels Conclusions: Our results suggest that, despite similar clinical and disease-related parameters, SSc patients who develop PAH have an unfavorable metabolic profile able to cause an impaired production of metabolites with protective effects on endothelial cells.